ARSITEKTUR UMA LULIK FUILORO, LOSPALOS KOTA, TIMOR-LESTE - maria immaculata ririk winandari; Andre Mariano Dos Santos Belo (MODUL, 2021)
Uma Lulik is a sacred house for the people of Timor-Leste. This house is the unification of Nain (owner, ruler or supreme), Beala (ancestor), Lulik (sacred "nature and its contents"), Lisan (tradition "family or human life".). Uma Lulik in Fuiloro is built or renovated every 10 to 20 years depending on the lia nain and fatal building problems that occur in Uma Lulik, to serve as a bond between families. Uma Lulik remains a comfortable place for people to carry out rituals with their ancestors, those who are here and those who have gone. The purpose of this study was to find the architectural characteristics of uma lulik in the fuiloro tribe, Lospalos City. Interpretive history method is used by looking at interpreting past conditions with the present. The result showed that Uma lulik in Fuiloro tribe characteristic has a single stilt-shaped building as a place for sacral ceremonies and storage of sacred goods. The interior consists of kitchen and Labor Dato. The shape of the roof is pointed with 55° as high as + 7m-9m. This building has square floor plan + 3m x 3m or + 4m x 4m, rectangular wall + 3m x 4m, and column of 4 round wood arrangements as high as + 3m-4m. Materials consist of ulin wood (ai-bessi), rose wood (ai-ná), acadiro (ai-acadirum), bamboo (au-maus), palapeira/palapa (ai-car) and gamuteira/ gamuti (au-naulurir). Ornaments are woven long ropes and carvings. Structural systems are ‘ikat’ and portal systems.